Деякі аспекти професійно-педагогічної компетентності вчителя в умовах нової української школи - Запорожцева, Юлія; Zaporozhtseva, Yu. (Східноєвропейський національний університет імені Лесі Українки, 2017)
Стаття присвячена дослідженню сутності професійно-педагогічної компетентності педагога в умовах Нової української школи. Автор аналізує поняття «професійна компетентність», «соціальна компетентність», «професійно-педагогічна компетентність» вчителя відповідно до викликів сучасного освітнього простору, указує на актуальні вимоги до педагога демократичної школи, називає основні ключові компетенції учителя з урахуванням динамічного розвитку суспільства. Стаття знайомить з основопокладаючими ознаками сучасного вчителя – професіонала відповідно до інноваційних вимог освітнього інформаційного середовища, наголошує на значущості самоосвіти педагога, його систематичній праці щодо саморозвитку й професійного самовдосконалення. Автор нагадує про сутність компетентнісного підходу, його вплив на навчально-виховний процес здобувача освітніх послуг та організацію освітнього простору, а також про набуття педагогом певного рівня життєвих компетентностей, відповідно й учнів. Перспективу подальших досліджень автор бачить у з’ясуванні чинників особистісної мотивації педагога, творчому й відповідальному його ставленні до власного безперервного професійного розвитку. In the article is analyzed the theoretical domestic and foreign material on the problem of the competent approach in education on the different levels. The author points to the actual requirements for the teacher of the modern democratic school, according to the adoption of the new Standard of Education of Ukraine and the Concept of the New Ukrainian School. The article is devoted to the study of the essence and significance of teacher's professionally-pedagogical competence in the context of reformation and modernization the education. The author names the basic key competences of the teacher, taking into account the dynamic development of the society, analyzes and raises the meanings and characteristics of the basic concepts: «professional competence», «social competence», «professionally-pedagogical competence» of the teacher, describes the criteria in accordance with the challenges of modern educational space. The work is underlined the needing for teacher a long life learning: their systematic development, improvement their skills and abilities, including skills of work with the modern information and communication technologies, constant enrichment with modern knowledge. The author mentions the importance of the competence approach, his influence on the educational and pedagogical process of the pupils and the organization of the learning process. Also, the level of life skills and skills of the teacher, which influences the perception of the teacher's personality as a student/pupil is important. The development of the modern information space puts for teachers new demands on their personal and professional development, to the level of their skills and abilities. The new Standard of education in Ukraine aims to improve the quality of education, and this increase involves the transformation of educational curricula, the motivation of participants in the learning process, the recognition of the ethical foundations and moral goals by the teacher, the expansion of his opportunities and professional skills, the improvement of pedagogical skills and, most importantly, in the author's opinion, the approval of the freedom of professional activity of the teacher. The author expects the following perspectives of research to study motives and reasons that positively influenced the creative and responsible attitude of the teacher to professional development.
The some aspects of teacher's professionally-pedagogical competence in the conditions of the New Ukrainian school
Keywords: професійна та соціальна компетентність; ключові компетентності; розвиток; навчальна діяльність; professional and social competence; the key competences; development; an educational activity